2013
DOI: 10.1016/j.tvjl.2013.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental infection in goats experimentally infected with a European strain of bluetongue virus serotype 8

Abstract: The capability of the current European strain of bluetongue virus serotype 8 (BTV-8) to cross the ruminant placenta has been established in experimental and field studies in both sheep and cattle. Sero-prevalence rates in goats in north-western Europe were high during the recent outbreak of BTV-8, however the capability of the virus to infect goats through the transplacental route has not been established. In the present study, four Saanen goats pregnant at 62 days of gestation were inoculated with the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
5
27
0
1
Order By: Relevance
“…The use of a uniform experimental framework has allowed us to rigorously interrogate both experimental questions addressed in past studies (55), as well as to explore hitherto unanswered questions. First of all, as suggested previously (24, 3236), we confirmed that while both sheep and goats are fully susceptible to BTV (in this case BTV-8) infection, the former are more susceptible than goats and more likely to develop clinical disease. The levels of viremia in BTV-infected goats were not different from (if anything, higher than) those observed in infected sheep.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The use of a uniform experimental framework has allowed us to rigorously interrogate both experimental questions addressed in past studies (55), as well as to explore hitherto unanswered questions. First of all, as suggested previously (24, 3236), we confirmed that while both sheep and goats are fully susceptible to BTV (in this case BTV-8) infection, the former are more susceptible than goats and more likely to develop clinical disease. The levels of viremia in BTV-infected goats were not different from (if anything, higher than) those observed in infected sheep.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, studies in sheep using as little as 10 1.4 TCID 50 were able to induce infection in this animal species (66). In two previous studies, also using BTV-8 isolates from the Netherlands, some of the experimentally infected goats developed mild clinical signs, fever, and viremia (34, 36). However, in both studies, goats were infected intravenously (34, 36), and in one of them animals were infected at day 62 of gestation (36).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Serological detection of BTV does not necessarily imply that animals are undergoing a period of active infection, as the levels of antibodies remain elevated for up to three years after the viral infection (PEARSON; JOCHIM, 1979). Only studies conducted in experimentally infected animals reported presence of the virus in the uterus (these studies isolated cows, performed in situ hybridization in female dogs and RT-PCR in goats) (BROWN et al, 1996;COETZEE et al, 2013;DE LA CONCHA-BERMEJILLO et al, 1993).…”
Section: Resultsmentioning
confidence: 99%